When snacks become meals: How hunger and environmental cues bias food intake - Shimizu Mitsuru; Payne Collin R; Wansink Brian (BMC, 2010)
Abstract Background While environmental and situational cues influence food intake, it is not always clear how they do so. We examine whether participants consume more when an eating occasion is associated with meal cues than with snack cues. We expect their perception of the type of eating occasion to mediate the amount of food they eat. In addition, we expect the effect of those cues on food intake to be strongest among those who are hungry. Methods One-hundred and twenty-two undergraduates (75 men, 47 women; mean BMI = 22.8, SD = 3.38) were randomly assigned to two experimental conditions in which they were offered foods such as quesadillas and chicken wings in an environment that was associated with either meal cues (ceramic plates, glasses, silverware, and cloth napkins at a table), or snack cues (paper plates and napkins, plastic cups, and no utensils). After participants finished eating, they were asked to complete a questionnaire that assessed their hunger, satiety, perception of the foods, and included demographic and anthropometric questions. In addition, participants' total food intake was recorded. Results Participants who were in the presence of meal-related cues ate 27.9% more calories than those surrounded with snack cues (416 versus 532 calories). The amount participants ate was partially mediated by whether they perceived the eating occasion to be a meal or a snack. In addition, the effect of the environmental cues on intake was most pronounced among participants who were hungry. Conclusions The present study demonstrated that environmental and situational cues associated with an eating occasion could influence overall food intake. People were more likely to eat foods when they were associated with meal cues. Importantly, the present study reveals that the effect of these cues is uniquely intertwined with cognition and motivation. First, people were more likely to eat ambiguous foods when they perceived them as a meal rather than a snack. Second, the effect of the environmental cues on intake was only observed among those who were hungry.